Synergistic Effect of Propolis and Antibiotics on Uropathogenic Escherichia coli - Jean-Philippe Lavigne; Jérémy Ranfaing; Catherine Dunyach-Rémy; Albert Sotto (MDPI AG, 2020)
Urinary tract infections (UTIs) are the most common bacterial infections around the world. Uropathogenic Escherichia coli (UPEC) is among the main pathogens isolated in UTIs. The rate of UPEC with high resistance towards antibiotics and multidrug-resistant bacteria have increased dramatically and conduct to the difficulty to treat UTIs. Due to the rarefaction of new antibiotics molecules, new alternative strategies must be evaluated. Since many years, propolis has demonstrated an interesting antibacterial activity against E. coli. Here, we evaluated its activity added to antibiotics on a panel of UPEC with different resistance mechanisms. Minimal inhibitory concentrations (MICs) and time-kill curves of fosfomycin, ceftriaxone, ertapenem and ofloxacin, with and without propolis, were determined. Significant diminution of the MICs was observed using ceftriaxone or ofloxacin + propolis. Propolis alone had a bacteriostatic activity with time-dependent effect against UPEC. The addition of this nutraceutical improved the effect of all the antibiotics evaluated (except fosfomycin) and showed a synergistic bactericidal effect (fractional inhibitory concentrations index ≤ 0.5 and a decrease ≥ 2 log CFU/mL for the combination of propolis plus antibiotics compared with the antibiotic alone). Propolis is able to restore in vitro antibiotic susceptibility when added to antibiotics against UPEC. This study showed that propolis could enhance the efficiency of antibiotics used in UTIs and could represent an alternative solution.